The Status of Rescinding Security Holders in Bankruptcy—The Proposed Bankruptcy Act of 1973 and Alternatives (Washington University Law Quarterly, 1975)
This Article will examine the present law on the status of security holders’ rescission claims in bankruptcy and analyze the various proposals for limiting such claims and the advisability of accommodating the bankruptcy and securities laws.
Keywords: Bankruptcy claims